Thriving in a male-dominated workplace - Dillard, Stephanie; Kersey, Amanda; Sheppard, Leah; Cardador, Teresa; Romero, Julia González; Massa, Cristina; Abrams, Stacey; Hodgson, Lara; Hoffman, Raven; Bohns, Vanessa K. (Ascent Audio, 2023)
Find success in a workplace dominated by men. Sexism. Self-doubt. Invisibility. When you're one of the only women in your workplace, it can be difficult to gain your footing. Organizations need to change, but in the meantime, women can find success in these settings-and even flourish in them. Thriving in a Male-Dominated Workplace provides the advice you need to ensure your professional growth in roles and industries that have traditionally been filled by and controlled by men. From connecting with the right people to growing your confidence to fighting back against bias, you'll be able to establish your credibility and be seen by your colleagues as the expert you are. This book will inspire you to: - Find support across the organization - Overcome impostor syndrome and self-doubt - Speak up for yourself and your accomplishments - Build a better culture-once and for all.